Inventarisasi Produk Pangan Fermentasi Lokal Pada Pasar Tradisional di Pontianak Sebagi Sumber Belajar Mikrobiologi - Hasria Alang; Yuyun Nisaul Khairillah; Ravi Aulia Febrianty; Ninda Novita; Dwi Febrianty Ningsih; Sultan Adi Pratama (Institut Agama Islam Negeri Kerinci, 2024)
West Kalimantan, renowned for its abundant biological natural resources, often utilizes them in local food production through fermentation, representing indigenous knowledge passed down through generations. The involvement of microbes in changing a substrate to produce certain products is related to the use of microbes in life, and is one of the themes in the Microbiology course. The aim of this research is to inventory the types of traditional foods typical of West Kalimantan, and their relation to learning Microbiology. Data collection techniques to obtain facts are carried out through observation, interviews and documentation with sources. Data analysis was carried out in a qualitative descriptive manner. The research results showed that the types of traditional food found at the research location were cincalok, wet shrimp paste, salted mustard greens, tempoyak, jasam, and mandai. Based on the research results, it was concluded that there are six traditional food products which constitute local wisdom of ethnic groups in Pontianak. The process of making these food products utilizes bacteria that are naturally present, which means it involves the concept of microbiology, which indicates that it can be used as a learning resource for microbiology courses in the form of modules.